The complete chloroplast genome of Rhododendron delavayi (Ericaceae). Issue 1 (2nd January 2020) - Liu, Jie; Chen, Ting; Zhang, Yubin; Li, Yuke; Gong, Jiyi; Yi, Yin
Abstract: Rhododendron delavayi, as a member of Ericaceae family, has been widely used as an important garden flower. The cp genome of R. delavayi exhibited a typical quadripartite cycle with 193, 798 bp, comprising of a pair of inverted repeats (IRa and IRb) of 15, 494 bp intersected by a large single copy (LSC) region of 160, 234 bp and a quite small single copy region of 2576 bp. Totally, 123 unique genes were assembled in this cp genome, including 80 protein genes, 35 tRNAs and 8 rRNAs. Out of these assembled genes, 88 genes (71.54%) were single copy. Phylogenetic analysis based on 14 cp genome of related species showed that the R. delavayi was closely related to Vaccinium oldhamii . This study provides important information for future evolution, genetic and molecular biology studies of Rhododendron .